2013
DOI: 10.1016/j.preteyeres.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anisometropia and amblyopia

Abstract: This review aims to disentangle cause and effect in the relationship between anisometropia and amblyopia. Specifically, we examine the literature for evidence to support different possible developmental sequences that could ultimately lead to the presentation of both conditions. The prevalence of anisometropia is around 20% for an inter-ocular difference of 0.5D or greater in spherical equivalent refraction, falling to 2-3%, for an inter-ocular difference of 3D or above. Anisometropia prevalence is relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 360 publications
(757 reference statements)
2
126
0
9
Order By: Relevance
“…There is no shortage of reviews of various aspects of amblyopia over the last decade (Birch, 2013; Hess, Babu, et al, 2014; Hess, Thompson, et al, 2014; Kiorpes, 2006; Levi, 2006; Webber & Wood, 2005; Wong, 2012: Barrett, Bradley, & Candy, 2013; Grant & Moseley, 2011; Levi, 2012; Levi, 2013; Levi & Li, 2009; Repka & Holmes, 2012). The focus of this review is on stereopsis and its potential for recovery in persons with amblyopia, specifically, we address the following issues:

How is stereopsis compromised in amblyopia?

Why does stereopsis matter?

Can stereopsis be recovered in children and adults with amblyopia?

…”
Section: Introductionmentioning
confidence: 99%
“…There is no shortage of reviews of various aspects of amblyopia over the last decade (Birch, 2013; Hess, Babu, et al, 2014; Hess, Thompson, et al, 2014; Kiorpes, 2006; Levi, 2006; Webber & Wood, 2005; Wong, 2012: Barrett, Bradley, & Candy, 2013; Grant & Moseley, 2011; Levi, 2012; Levi, 2013; Levi & Li, 2009; Repka & Holmes, 2012). The focus of this review is on stereopsis and its potential for recovery in persons with amblyopia, specifically, we address the following issues:

How is stereopsis compromised in amblyopia?

Why does stereopsis matter?

Can stereopsis be recovered in children and adults with amblyopia?

…”
Section: Introductionmentioning
confidence: 99%
“…Strabismus, one of the principal ocular deficits in low-income children (29,30) , is characterized by dysfunction of the extraocular muscles, generating binocular misalignment. The strabismic eye may fail to receive visual stimuli onto the macular area (31) , thus affecting various developmental stages of cortical processing (16) .…”
Section: Strabismusmentioning
confidence: 99%
“…As a form of treatment independent of occlusion, some studies have reported the use of atropine (Table 2), a parasympatholytic muscarinic antagonist. Atropine may help in treating moderate amblyopia (29) , as it interferes with visual accommodation of the fellow normal eye, thus indirectly forcing use of the amblyopic one (19) . However, atropine treatment is not always effective (48) .…”
Section: Main Treatmentsmentioning
confidence: 99%
“…Mit höherer Kurzsichtigkeit ist auch das häufigere Auftreten einer Amblyopie verbunden [7]. Das hängt nicht zuletzt damit zusammen, dass die Rate höherer Anisometropien auf weit über 10 % in der Gruppe mit hohen Ametropien anwächst [56].…”
Section: Kurzsichtigkeit Und Schielenunclassified